#Allhandsondeck Shaun King and unite the right rally: mobilization and the networked social journalist. - Bashri, Maha; Zaki, Nazar (Atlantic Journal of Communication)
Alternative media has provided space for the disenfranchised, where counterhegemony and political practice can take place. Social media platforms have allowed for the formation of new communicative space that disrupts power structures and the established flow of information. This has allowed individuals, who share similar values and ideas, to come together in newly formed public spheres. Furthermore, it has allowed for the emergence of a new type of "social" journalist, who can rally and mobilize audiences around issues beyond the confines of the virtual world. The following study is based on a network analysis of Shaun King's mobilization of followers on Twitter (August 11–13, 2017) after the Unite the Right rally in Charlottesville, Virginia.